Portraits of Allies and Enemies in the Dynastic Galleries of Queen Mary of Hungary - Martínez Marín, Cruz María (Eikón / Imago, 2020)
Mary of Hungary was one of the biggest collectors of 16th century Europe. By commissioning paintings from great artists, she exhibited multiple portrait galleries in her palaces, a phenomenon that became popular in the Early Modern Age. It is known, from the portraits that have come to our time, that notorious enemies stood among them. This paper examines primary and secondary sources with the intention of pointing out where these galleries were located and what function these portraits should have fulfilled within them. It is concluded that the dynastic galleries commissioned by the Queen celebrate the influence that the Habsburgs achieved in European courts thanks to marriage policy and also, her rol as imperial advisor.
Keywords: Mary of Hungary; Dynastic Galleries; Portraits; Titian; Renaissance